Pengaruh Kualitas Layanan dan Fasilitas Terhadap Loyalitas Dengan Kepuasan Pasien Rawat Jalan Sebagai Intervening Di Klinik Fast Medika Center - Tao Putri; Theresia Pradiani; Fathorrahman (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study is to influence service quality and facilities on loyalty with patient satisfaction as an intervening variable at the Klinik Fast Medika Center. The data used in this study are primary data obtained from the results of questionnaires. The sample in this study is 73 outpatients, with the sampling technique using purposive sampling. The data analysis technique used in this study is path analysis and the Sobel test using SPSS 25.0. The results show that service quality has a significant effect on patient satisfaction, facilities have a significant effect on patient satisfaction, there is an effect of patient satisfaction on loyalty, there is an influence of service quality on satisfaction, there is an influence of facilities on patient satisfaction, service quality influences loyalty through patient satisfaction and facilities influences loyalty through patient satisfaction.